Palladium-carbon catalyst as well as preparation method and application thereof
By loading palladium and ruthenium on the activated carbon support, controlling the proportion of Pd(111) crystal surface atoms, and combining acid pretreatment, the active site utilization rate of palladium carbon catalyst is improved, and the insufficient activity of Pd nanoparticles in the prior art is solved. and the problem of high precious metal content, the effect of efficient removal of impurities in crude terephthalic acid and reducing costs is achieved.
Patent Information
- Application Number
- CN202310776357.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-28
AI Technical Summary
The existing palladium carbon catalysts have low surfactant atom utilization rate of Pd nanoparticles in the hydrogenation reaction, resulting in high Pd content and high cost of precious metals, and it is difficult to effectively remove the impurities of para-carboxybenzaldehyde in crude terephthalic acid.
By simultaneously loading metal palladium and metal ruthenium on activated carbon support, controlling the proportion of Pd(111) crystal atoms in the range of 25%-75%, combining acid pretreatment and specific steps to build a suitable Pd grain surface The atom exposure ratio increases the utilization rate of Pd active sites and uses Ru atoms to enhance catalytic activity.
The content of precious metal Pd is significantly reduced, the reaction effect and economy of the catalyst is improved, and the 4-CBA in crude terephthalic acid is effectively removed, thereby reducing the catalyst preparation cost.
Smart Images

Figure CN119215887A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts, and specifically relates to a palladium-carbon catalyst and a preparation method and application thereof. Background Art
[0002] Purified terephthalic acid, commonly known as PTA, is the basic raw material for the synthesis of polyethylene terephthalate. Crude terephthalic acid (CTA) contains a small amount of impurity p-carboxybenzaldehyde (4-CBA), which will affect the subsequent esterification performance of PTA. The method for effectively removing 4-CBA contained in CTA in industry is to hydrogenate 4-CBA into hydroxymethylbenzoic acid and p-toluic acid, which are easily soluble in water, under the action of palladium catalyst, and then separate and purify CTA through multiple crystallization and centrifugation. The catalyst currently used in industry is mainly palladium-carbon catalyst. During the hydrogenation catalytic process, only a few surface active atoms in Pd nanoparticles participate in the reaction, resulting in a significant reduction in the utilization rate of Pd atoms. Therefore, the preparation method of the catalyst and the distribution of metal palladium on the carrier have a great influence on the performance of the catalyst. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a palladium carbon catalyst and a preparation method of the palladium carbon catalyst. When the palladium carbon catalyst provided by the present invention is used in the hydrogenation refining of crude terephthalic acid, the content of residual p-carboxybenzaldehyde can be effectively reduced.
[0004] In a first aspect, the palladium-carbon catalyst provided by the present invention comprises an activated carbon carrier and metal palladium and metal ruthenium loaded on the carrier, wherein in the catalyst, the proportion of atoms exposing the Pd(111) crystal plane is 25%-75%, for example, 27%, 30%, 33%, 35%, 37%, 40%, 43%, 45%, 47%, 49%, 50%, 51%, 53%, 55%, 57%, 59%, 60%, 61%, 63%, 65%, 67%, 69%, 70%, 72%, 74% or any value therebetween. The present invention simultaneously loads metal palladium and metal ruthenium on an activated carbon carrier, and controls the atomic ratio of the exposed Pd (111) crystal plane within the above range. On the one hand, the presence of ruthenium provides a confined platform for the growth of Pd nanoparticles, limits the atomic ratio of the (111) surface of the Pd nanoparticles within a suitable range, so that the surface of the Pd nanoparticles has sufficient active sites for reactant adsorption and desorption, and the number of atoms that do not participate in the reaction inside the particles is minimized, thereby improving the utilization rate of Pd under the same loading amount. On the other hand, the hydrogen overflow effect of Pd makes Ru atoms with relatively low hydrogenation activity also have high activity, so that the catalyst has better comprehensive reaction effect and lower cost.
[0005] In some embodiments, the atomic percentage of exposed Pd (111) crystal planes in the catalyst is 30%-75%.
[0006] In some embodiments, the atomic percentage of exposed Pd (111) crystal planes in the catalyst is 45% to 65%.
[0007] In some embodiments, the mass content of the metal palladium is 0.1%-0.5% based on the mass of the catalyst. In some embodiments, the mass content of the metal palladium is 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or any value therebetween.
[0008] In some embodiments, the mass content of the metal ruthenium is 0.1%-0.5% based on the mass of the catalyst. In some embodiments, the mass content of the metal ruthenium is 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or any value therebetween.
[0009] In a second aspect, the preparation method of the palladium-carbon catalyst provided by the present invention comprises:
[0010] S1: providing an acid pretreated activated carbon support;
[0011] S2: mixing the activated carbon carrier with a solution containing a ruthenium source to obtain a first mixed solution;
[0012] S3: mixing the first mixed solution with a complexing agent, and then mixing with a solution containing a palladium source to obtain a second mixed solution;
[0013] S4: leaving the second mixed solution to stand, dry, and restore.
[0014] The method of the present invention effectively constructs a suitable atomic exposure ratio on the surface of Pd grains by first loading ruthenium element and then loading palladium element on the activated carbon carrier, efficiently utilizes Pd active sites, and successfully achieves the purpose of reducing the content of precious metal Pd and efficiently removing 4-CBA.
[0015] In some embodiments, in S1, the acid pretreatment includes reacting the activated carbon with an oxidizing acid and then calcining it. Acid pretreatment of the activated carbon before loading can enrich the surface of the carbon layer with more carboxyl and carbonyl functional groups. The relevant functional groups can electrostatically adsorb Ru cations in the corresponding pH range to construct a more dispersed RuO particle platform, and then Pd nanoparticles can be more evenly grown and regulated.
[0016] In some embodiments, the oxidizing acid comprises at least one of nitric acid, sulfuric acid and perchloric acid. In some embodiments, the oxidizing acid is selected from nitric acid with a concentration of 40%-60%, such as 50% or 55%.
[0017] In some embodiments, the calcination temperature is 400° C.-600° C., for example, 450° C., 500° C. or 550° C. In some embodiments, the calcination is performed under the protection of an inert gas. In some embodiments, the inert gas is selected from nitrogen and / or argon.
[0018] In some embodiments, the mixing in S2 is performed at room temperature, for example, at a temperature of 5°C-35°C.
[0019] In some embodiments, the first mixed solution and the complexing agent in S3 are mixed at room temperature, for example, 5° C.-35° C. In some embodiments, after the first mixed solution and the complexing agent are mixed in S3, they are allowed to stand at room temperature, for example, 5° C.-35° C. for a certain period of time, for example, 2 h-10 h, and then mixed with the solution containing the palladium source. Preferably, the mixing is carried out at room temperature, for example, 5° C.-35° C.
[0020] In some embodiments, the activated carbon carrier is selected from one or more of coal charcoal, wood charcoal or fruit shell charcoal. In some embodiments, the activated carbon carrier is selected from coconut shell activated carbon.
[0021] In some embodiments, the activated carbon specific surface area is preferably 800 m 2 / g-1600m 2 / g, for example but not limited to the activated carbon specific surface area of 900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g and so on.
[0022] In some embodiments, the activated carbon pore volume is 0.35 mL / g-0.80 mL / g, for example but not limited to the activated carbon pore volume of 0.4 mL / g, 0.45 mL / g, 0.5 mL / g, 0.55 mL / g, 0.6 mL / g, 0.65 mL / g, 0.mL / g, 0.75 mL / g and the like.
[0023] In some embodiments, in the solution containing a ruthenium source and the solution containing a palladium source, the mass ratio of the palladium element to the ruthenium element is (0.2-4): 1. In some embodiments, the mass ratio of the palladium element to the ruthenium element is 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or any value therebetween.
[0024] In some embodiments, the ruthenium source is selected from RuCl3 and its ammonia complex. In some embodiments, the pH of the solution containing the ruthenium source is 1-12, for example, 2, 4, 6, 7, 8.5, 9, 9.5, 10, 10.5, 11 or 11.5. In some embodiments, the pH of the solution containing the ruthenium source is 8-12. Alkaline solutions containing ruthenium sources are conducive to the synthesis of the catalyst of the present invention.
[0025] In some embodiments, the palladium source is selected from H2PdCl4 and its hydrochloric acid complex. In some embodiments, the pH of the solution containing the palladium source is 1-12, for example, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 9 or 11. In some embodiments, the pH of the solution containing the palladium source is 1-6. Acidic solutions of palladium-coated ruthenium sources are conducive to the dispersion of palladium. In some embodiments, in the solution containing the ruthenium source, the mass of the ruthenium source is 0.1%-0.5% of the acid-pretreated activated carbon support, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or any value therebetween, based on the mass of the ruthenium element.
[0026] In some embodiments, in the solution containing a palladium source, the mass of the palladium source, calculated as the mass of the palladium element, is 0.1%-0.5% of the acid-pretreated activated carbon support, for example, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or any value therebetween.
[0027] In some embodiments, the complexing agent is selected from at least one of 8-hydroxyquinoline, ethylenediaminetetraacetic acid, and pyromellitic acid.
[0028] In some embodiments, the mass ratio of the complexing agent to the acid pretreated activated carbon carrier is (0.5-15):50, for example, 1.5:50, 2:50, 3:50, 4:50, 5:50, 6:50, 7:50, 8:50, 9:50, 9.5:50, 11:50, 12:50, 14:50 or any value therebetween. In some embodiments, the mass ratio of the complexing agent to the acid pretreated activated carbon carrier is (1-10):50. In some embodiments, in S4, the standing temperature is 10°C-30°C, for example, 15°C, 20°C or 25°C. In some embodiments, in S4, the standing time is 1h-10h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h or 9h.
[0029] In some embodiments, in S4, the drying temperature is 50°C-150°C, for example, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or 140°C.
[0030] In some embodiments, in S4, the reduction conditions include: reduction in a mixed gas atmosphere of hydrogen and argon, wherein the volume concentration of hydrogen is 0.5%-5%. In some embodiments, the volume concentration of hydrogen is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or any value therebetween.
[0031] In some embodiments, the flow rate of the hydrogen and argon mixture is 1 mL / min-40 mL / min, for example, 5 mL / min, 10 mL / min, 15 mL / min, 20 mL / min, 25 mL / min, 30 mL / min or 35 mL / min.
[0032] In some embodiments, in S4, the reduction time is 1 h-5 h, such as 2 h, 3 h or 4 h. In some embodiments, in S4, the reduction temperature is 150°C-300°C, such as 180°C, 200°C, 220°C, 240°C, 260°C or 280°C.
[0033] In some embodiments, the method comprises purging with a gas mixture comprising oxygen and argon after the reduction reaction. In some embodiments, the volume concentration of oxygen in the gas mixture comprising oxygen and argon is 0.5%-5%. In some embodiments, the volume concentration of oxygen is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or any value therebetween.
[0034] In some embodiments, the flow rate of the mixed gas is 1 mL / min-40 mL / min, for example, 5 mL / min, 10 mL / min, 15 mL / min, 20 mL / min, 25 mL / min, 30 mL / min or 35 mL / min.
[0035] In some embodiments, the purging temperature is 80° C.-150° C., for example, 90° C., 100° C., 110° C., 120° C., 130° C. or 140° C. In some embodiments, the purging time is 0.5 h-3 h, for example, 1 h, 1.5 h, 2 h or 2.5 h.
[0036] In some embodiments, the preparation method of the palladium-carbon catalyst comprises the following specific steps:
[0037] (a) reacting the activated carbon with an oxidizing acid and then calcining the activated carbon to obtain a pretreated carrier
[0038] (b) providing a solution A comprising a ruthenium source and a solution B comprising a palladium source;
[0039] (c) first dripping solution A into the pretreated carrier, adding the complexing agent, then adding solution B, standing at room temperature, and then heating to dry;
[0040] (d) reducing the dry solid with hydrogen and then purging it in a mixed gas of oxygen to obtain a finished catalyst.
[0041] In a third aspect, the present invention provides the use of the palladium-carbon catalyst described in the first aspect or the palladium-carbon catalyst prepared by the preparation method described in the second aspect in the hydrogenation refining of crude terephthalic acid.
[0042] In a fourth aspect, the present invention provides a method for hydrogenating and refining crude terephthalic acid, which comprises using water as a solvent, crude terephthalic acid containing 4-CBA and hydrogen as raw materials, reacting in the presence of the palladium-carbon catalyst described in the first aspect or the palladium-carbon catalyst prepared by the preparation method described in the second aspect, to remove 4-CBA in the crude terephthalic acid.
[0043] In some embodiments, the hydrofinishing reaction temperature may be 250° C.-295° C., such as 265° C.-290° C. In some embodiments, the hydrofinishing reaction pressure may be 6.5 MPa-10.0 MPa, such as 7.0 MPa-9.0 MPa. In some embodiments, the hydrogen partial pressure may be 0.5 MPa-1.0 MPa.
[0044] In some embodiments, the reaction can be carried out in a batch operation or a continuous operation.
[0045] Beneficial technical effects of the present invention:
[0046] By adjusting the loading method of Pd and Ru elements, the appropriate atomic exposure ratio of Pd grain surface was effectively constructed, and Pd active sites were efficiently utilized, successfully achieving the goal of reducing the content of precious metal Pd and efficiently removing 4-CBA. Compared with the traditional palladium carbon catalyst with a loading of 0.5wt%, the cost is greatly reduced and the economic efficiency is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the HAADF-STEM image of the palladium-carbon catalyst of Example 1 of the present invention. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments and drawings. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation to the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0049] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0050] The present invention will be described in detail below through examples.
[0051] In the present invention, the position of Pd nanoparticles is determined by EDS scanning using HAADF-STEM, and then the particle size and morphology of 200 Pd nanoparticles are randomly counted to determine the atomic ratio of exposed Pd (111) crystal plane in the palladium-carbon catalyst, wherein the specific method for calculating the number of crystal plane atoms is as follows:
[0052]
[0053] The diameter of a Pd atom is d Pd is 0.276nm, and the relationship between the number of Pd atoms in the cubic octahedron and the average particle size of its nanoparticles is:
[0054] d=1.105×N T 1 / 3 ×d Pd atom
[0055] The number of atoms on the Pd(111) surface = N 111 / N S
[0056] Example 1
[0057] 1. Catalyst preparation
[0058] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. The above activated carbon was sealed and mixed with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and calcined, recorded as AC-D;
[0059] (b) Prepare RuCl3 aqueous solution (in terms of Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (in terms of Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add ammonia water to adjust the pH to 12, which is recorded as solution A; take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and use HCl (0.5 mol / L) solution to adjust the pH to 1, which is recorded as solution B;
[0060] (c) Then, solution A was added dropwise to 50 g AC-D and stirred continuously for 1 h, and then 5 g 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution B was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0061] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0062] The preparation conditions are listed in Table 1.
[0063] 2. Catalyst evaluation
[0064] The evaluation was performed using an intermittent stirred tank, with the following specific conditions:
[0065] Catalyst loading mass: 2g;
[0066] Reaction raw material composition: 30g crude terephthalic acid, pure water, 10g 4-CBA;
[0067] Reaction pressure: 7.5MPa;
[0068] Reaction temperature: 280°C;
[0069] Reaction time: 30min;
[0070] Catalyst evaluation method:
[0071] The activity evaluation of the catalyst was carried out in a 2L batch reactor. The reaction raw materials were put into the reactor, and the catalyst was loaded into the rotating frame in the reactor. The reaction conditions were as described above, and the hydrogen partial pressure was 1MPa. After the reaction was completed, the hydrorefined terephthalic acid was washed with ultrapure water, filtered, dried, and sampled to detect the 4-CBA content. The 4-CBA content was detected using an HP1100 HPLC instrument and the experimental results are listed in Table 2.
[0072] Example 2
[0073] 1. Catalyst preparation
[0074] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. It was mixed and stirred with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and recorded as AC-D;
[0075] (b) Prepare RuCl3 aqueous solution (in terms of Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (in terms of Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add HCl (0.5 mol / L) dropwise to adjust the pH to 1, which is recorded as solution A; take 17.5 ml of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and adjust the pH to 12 with ammonia water, which is recorded as solution B;
[0076] (c) Then, solution A was added dropwise to 50 g AC-D and stirred continuously for 1 h, and then 5 g 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution B was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0077] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0078] The preparation conditions are listed in Table 1.
[0079] 2. Catalyst evaluation
[0080] The evaluation was performed using an intermittent stirred tank, with the following specific conditions:
[0081] Catalyst loading mass: 2g;
[0082] Reaction raw material composition: 30g crude terephthalic acid, pure water, 10g 4-CBA;
[0083] Reaction pressure: 7.5MPa;
[0084] Reaction temperature: 280°C;
[0085] Reaction time: 30min;
[0086] The catalyst evaluation method was the same as in Example 1.
[0087] The experimental results are listed in Table 2.
[0088] Example 3
[0089] 1. Catalyst preparation
[0090] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. The above activated carbon was sealed and mixed with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and calcined, recorded as AC-D;
[0091] (b) Prepare RuCl3 aqueous solution (in terms of Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (in terms of Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add ammonia water to adjust the pH to 9, which is recorded as solution A; take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and use HCl (0.5 mol / L) solution to adjust the pH to 4, which is recorded as solution B;
[0092] (c) Then, solution A was added dropwise to 50 g AC-D and stirred continuously for 1 h, and then 5 g 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution B was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0093] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0094] The preparation conditions are listed in Table 1.
[0095] 2. Catalyst evaluation
[0096] Same as Example 1.
[0097] Example 4
[0098] 1. Catalyst preparation
[0099] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. The above activated carbon was sealed and mixed with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and calcined, recorded as AC-D;
[0100] (b) Prepare RuCl3 aqueous solution (in terms of Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (in terms of Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add ammonia water to adjust the pH to 12, which is recorded as solution A; take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and use HCl (0.5 mol / L) solution to adjust the pH to 1, which is recorded as solution B;
[0101] (c) Then, solution A was added dropwise to 50 g AC-D and stirred continuously for 1 h, and then 10 g 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution B was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0102] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0103] The preparation conditions are listed in Table 1.
[0104] 2. Catalyst evaluation
[0105] Same as Example 1.
[0106] Comparative Example 1
[0107] 1. Catalyst preparation
[0108] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. It was mixed and stirred with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and recorded as AC-D;
[0109] (b) Prepare RuCl3 aqueous solution (Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make the volume 50 mL, then add ammonia water to adjust the pH to 12, which is recorded as solution A; take 17.5 mL of H2PdCl4 solution and add 17.5 mL of RuCl3 solution to make the volume 50 mL. l4 The aqueous solution was made up to 50 mL by adding pure water, and the pH was adjusted to 1 with HCl (0.5 mol / L), which was recorded as solution B;
[0110] (c) Then, solution B was added dropwise to 50 g AC-D and stirred continuously for 1 h, and then 5 g 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution A was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0111] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0112] The preparation conditions are listed in Table 1.
[0113] 2. Catalyst evaluation
[0114] The evaluation was performed using an intermittent stirred tank, with the following specific conditions:
[0115] Catalyst loading mass: 2g;
[0116] Reaction raw material composition: 30g crude terephthalic acid, pure water, 10g 4-CBA;
[0117] Reaction pressure: 7.5MPa;
[0118] Reaction temperature: 280°C;
[0119] Reaction time: 30min;
[0120] The catalyst evaluation method was the same as in Example 1.
[0121] The experimental results are listed in Table 2.
[0122] Comparative Example 2
[0123] 1. Catalyst preparation
[0124] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. The above activated carbon was sealed and mixed with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and calcined, recorded as AC-D;
[0125] (b) Prepare RuCl3 aqueous solution (in terms of Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (in terms of Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add HCl (0.5 mol / L) dropwise to adjust the pH to 1, which is recorded as solution A; take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and adjust the pH to 12 with ammonia water, which is recorded as solution B;
[0126] (c) Then, solution B was added dropwise to 50 g AC-D and stirred continuously for 1 h, and then 1 g 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution A was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0127] (d) The dried solid was placed in a tube furnace, H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to O2 / Ar mixed gas and introduced for 1 h. The preparation conditions are listed in Table 1.
[0128] 2. Catalyst evaluation
[0129] Same as Example 1.
[0130] Comparative Example 3
[0131] 1. Catalyst preparation
[0132] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. It was mixed and stirred with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and recorded as AC-D;
[0133] (b) Prepare RuCl3 aqueous solution (in terms of Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (in terms of Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add ammonia water to adjust the pH to 1, which is recorded as solution A; take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and use HCl (0.5 mol / L) solution to adjust the pH to 12, which is recorded as solution B;
[0134] (c) Then, solutions A and B were added dropwise to 50 g AC-D and stirred for 2 h, and then 5 g 8-hydroxyquinoline was added, followed by standing at 25 °C for 6 h and drying at 120 °C for 12 h;
[0135] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0136] The preparation conditions are listed in Table 1.
[0137] 2. Catalyst evaluation
[0138] The evaluation was performed using an intermittent stirred tank, with the following specific conditions:
[0139] Catalyst loading mass: 2g;
[0140] Reaction raw material composition: 30g crude terephthalic acid, pure water, 10g 4-CBA;
[0141] Reaction pressure: 7.5MPa;
[0142] Reaction temperature: 280°C;
[0143] Reaction time: 30min;
[0144] The catalyst evaluation method was the same as in Example 1.
[0145] The experimental results are listed in Table 2.
[0146] Comparative Example 4
[0147] 1. Catalyst preparation
[0148] (a) Prepare RuCl3 aqueous solution (Ru, 0.01 g / mL) and H2PdCl4 aqueous solution (Pd, 0.01 g / mL). Take 7.5 mL of RuCl3 solution and add pure water to make up to 50 mL, then add ammonia water to adjust the pH to 12, which is recorded as solution A; take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and use HCl (0.5 mol / L) solution to adjust the pH to 1, which is recorded as solution B;
[0149] (b) Then, solution A was added dropwise to 50 g of activated carbon and stirred continuously for 1 h, and then 10 g of 8-hydroxyquinoline was added, followed by standing at 25° C. for 6 h. Then, solution B was immediately added dropwise to the solid, stirred continuously for 1 h, and then stood at 25° C. for 6 h and dried at 120° C. for 12 h;
[0150] (c) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0151] The preparation conditions are listed in Table 1.
[0152] 2. Catalyst evaluation
[0153] Same as Example 1.
[0154] Comparative Example 5
[0155] 1. Catalyst preparation
[0156] (a) Weigh 50 g of 4-8 mesh coconut shell activated carbon flakes with a specific surface area of 1100 m 2 / g, pore volume is 0.6mL / g. The above activated carbon was sealed and mixed with 500mL concentrated nitric acid (50%) in a stirred tank for 1h, and then filtered and washed with a large amount of pure water until the filtrate was neutral. After drying in an oven at 100℃ for 6h, it was placed in a muffle furnace with inert gas at 500℃ and calcined, recorded as AC-D;
[0157] (b) Prepare H2PdCl4 aqueous solution (0.01 g / mL in terms of Pd). Take 17.5 mL of H2PdCl4 aqueous solution and add pure water to make up to 50 mL, and adjust the pH to 1 with HCl (0.5 mol / L), which is recorded as solution B;
[0158] (c) Solution B was then added dropwise to 50 g AC-D and stirred continuously for 1 h, followed by standing at 25 °C for 6 h and drying at 120 °C for 12 h;
[0159] (d) The dried solid was placed in a tube furnace, and a H2 / Ar (1%) mixed gas was introduced at a rate of 20 mL / min, and reduced at 280°C for 1 h; the temperature was lowered to 100°C, and then the gas was switched to an O2 / Ar mixed gas and introduced for 1 h.
[0160] The preparation conditions are listed in Table 1.
[0161] 2. Catalyst evaluation
[0162] Same as Example 1.
[0163] Table 1
[0164]
[0165] Table 2
[0166]
[0167] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A palladium-carbon catalyst comprising an activated carbon carrier and metal palladium and metal ruthenium supported on the carrier, wherein: In the catalyst, the atomic proportion of exposed Pd (111) crystal plane is 25%-75%.
2. The palladium-carbon catalyst according to claim 1, characterized in that The atomic proportion of exposed Pd (111) crystal plane is 30%-75%, preferably 45%-65%.
3. The palladium-carbon catalyst according to claim 1 or 2, characterized in that Based on the mass of the catalyst, the mass content of the metal palladium is 0.1%-0.5%; and / or the mass content of the metal ruthenium is 0.1%-0.5%.
4. A method for preparing a palladium-carbon catalyst, comprising: S1: providing an acid pretreated activated carbon support; S2: mixing the activated carbon carrier with a solution containing a ruthenium source to obtain a first mixed solution; S3: mixing the first mixed solution with a complexing agent, and then mixing with a solution containing a palladium source to obtain a second mixed solution; S4: leaving the second mixed solution to stand, dry, and restore.
5. The preparation method according to claim 4, characterized in that: In S1, the acid pretreatment includes reacting the activated carbon with an oxidizing acid and then calcining it. Preferably, the oxidizing acid comprises at least one of nitric acid, sulfuric acid and perchloric acid. Preferably, the calcination temperature is 400°C-600°C.
6. The preparation method according to claim 4 or 5, characterized in that: In the solution containing the ruthenium source and the solution containing the palladium source, the mass ratio of the palladium element to the ruthenium element is (0.2-4):1; and / or The ruthenium source is selected from RuCl3 and its ammonia complex, and the palladium source is selected from H2PdCl4 and its hydrochloric acid complex; and / or The pH of the solution containing the ruthenium source is 1-12, preferably 8-12; and / or The pH of the solution containing the palladium source is 1-12, preferably 1-6; and / or The complexing agent is selected from at least one of 8-hydroxyquinoline, ethylenediaminetetraacetic acid and pyromellitic acid.
7. The preparation method according to any one of claims 4 to 6, characterized in that: In S4, the standing temperature is 10°C-30°C, and the standing time is 1h-10h; and / or The drying temperature is 50°C-150°C.
8. The preparation method according to any one of claims 4 to 7, characterized in that: In S4, the reduction conditions include: reduction in a mixed gas atmosphere of hydrogen and argon, wherein the volume concentration of hydrogen is 0.5%-5%, the reduction time is 1h-5h, and the reduction temperature is 150°C-300°C.
9. Application of the palladium-carbon catalyst described in any one of claims 1 to 3 or the palladium-carbon catalyst prepared by the preparation method described in any one of claims 4 to 8 in the hydrogenation refining of crude terephthalic acid.
10. A method for hydrogenating and refining crude terephthalic acid, comprising using water as a solvent, crude terephthalic acid containing 4-CBA and hydrogen as raw materials, reacting in the presence of a palladium-carbon catalyst as described in any one of claims 1 to 3 or a palladium-carbon catalyst prepared by the preparation method as described in any one of claims 4 to 8, to remove 4-CBA from the crude terephthalic acid.
Citation Information
Patent Citations
Preparation method of low-loading-capacity ultra-small-size palladium / carbon catalyst for selective hydrogenation
CN103877974A
Crude terephthalic acid hydrofining catalyst
CN105268434A
Supported nano palladium cubic catalyst, preparation method thereof and application in synthesis of hydrogen peroxide
CN109420495A
Catalyst as well as preparation method and application thereof
CN114367282A
Pd / C Hydrogenetion Catalyst for Purifying TerephthalicAcid
KR1020050069180A
Cited By
A palladium-on-carbon catalyst for the hydrogenation purification reaction of terephthalic acid and its preparation method
CN122974334A
